2014
DOI: 10.1111/ajps.12166
|View full text |Cite
|
Sign up to set email alerts
|

Can Incarcerated Felons Be (Re)integrated into the Political System? Results from a Field Experiment

Abstract: How does America's high rate of incarceration shape political participation? Few studies have examined the direct effects of incarceration on patterns of political engagement. Answering this question is particularly relevant for the 93% of formerly incarcerated individuals who are eligible to vote. Drawing on new administrative data from Connecticut, we present evidence from a field experiment showing that a simple informational outreach campaign to released felons can recover a large proportion of the reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…This surprising relationship may be explained by the fact that many who lacked photo identification received an informational mailer from the Department of Elections informing them of the law and instructing them on how to acquire photo identification, as the significant increase in turnout we observe is consolidated in places that received more of these mailings. This is consistent with evidence from other recent studies that find that informational mailings from the state can increase turnout among marginalized and potentially misinformed populations (Gerber et al 2013(Gerber et al , 2015Meredith & Morse 2015).…”
Section: Discussionsupporting
confidence: 92%
“…This surprising relationship may be explained by the fact that many who lacked photo identification received an informational mailer from the Department of Elections informing them of the law and instructing them on how to acquire photo identification, as the significant increase in turnout we observe is consolidated in places that received more of these mailings. This is consistent with evidence from other recent studies that find that informational mailings from the state can increase turnout among marginalized and potentially misinformed populations (Gerber et al 2013(Gerber et al , 2015Meredith & Morse 2015).…”
Section: Discussionsupporting
confidence: 92%
“…States differ substantially in when and how formerly incarcerated individuals regain the right to vote.Consequentially, eligible formerly incarcerated individuals may incorrectly believe that they are disenfranchised(Meredith and Morse 2014). Supporting this account,Gerber et al (2015) show that outreach to eligible released felons can increase their registration and voting rates.…”
mentioning
confidence: 87%
“…At the same time, observing somewhat different patterns in Connecticut and Pennsylvania suggests that state context may still shape how incarceration affects turnout. Given Gerber et al's (2015) finding that mobilization is important for getting ex-felons to vote, particularly among the subset that participated previously, it would be useful to investigate whether the lower rate of participation among released prisoners in Connecticut is because that state was less contested in the presidential election than Pennsylvania, a characterization which is supported by the fact that average turnout rates declined more in Connecticut than in Pennsylvania. If context is important, applying approach three to Connecticut (if the data were available) would also allow us to understand how context is important.…”
Section: External Validitymentioning
confidence: 99%
“…() and Burch () found that selection bias and measurement error inflated the effects of serving time in prison on voting, producing a negative association larger than the true effect. Scholars have also found that outreach to felons considerably decreased the negative effects associated with incarceration (Gerber et al., ). There are also limitations associated with utilizing self‐reports of political participation.…”
Section: The Effects Of Carceral Contact On Participation: Some Mechamentioning
confidence: 99%